OnlineBioinfo: Leveraging the Teaching of Programming Skills to Life Science Students Through Learning Analytics - de Melo-Minardi, Raquel C.; de Melo, Eduardo C.; Bastos, Luana L. (Frontiers in Education, 2022)
Online learning has grown in recent years and has become popular with Massive Open Online Courses (MOOCs). The advent of the pandemic has undoubtedly made more teachers and students experience the online learning experience. Distance learning is going to grow even more in the coming years. In this article, we present our computational thinking and programming course focused in life science students. We introduce our approach for analyzing how students interact with didactic resources regarding their probability of completing the course. We discussed several insights this strategy brought us and how we can leverage the teaching of programming skills to life science students through learning analytics. We believe that machine learning techniques will be increasingly essential for better monitoring and supporting students and for online courses improvements.